(untitled) (REMUNOM, 2025)
Nematophagous fungi are capable of developing trap-like structures to capture and destroy the infective stages of nematodes. The aim of the present study was to analyze radial mycelial growth, sporulation, and Colony-Forming Units (CFUs) in Arthrobotrys musiformis, Arthrobotrys robusta, Arthrobotrys oligospora, Monacrosporium eudermatum, Monacrosporium elegans, Pochonia chlamydosporia, Dactylella leptospora, and Paecilomyces lilacinus, using six solid culture media and two liquid media, with four replicates for each treatment. The experiments were conducted in a BOD-type chamber, in the dark, at a temperature of 25 ± 1°C, in the Nematology Laboratory of the Faculty of Agricultural and Veterinary Sciences (FCAV/UNESP), municipality of Jaboticabal, São Paulo state, Brazil. The solid media were incubated for 15 days, with measurements taken every 48 hours (up to 288 hours). The liquid media were incubated under the same conditions for 21 days, subjected to homogenization and serial dilutions for CFU counting. Means were compared using Duncan’s test at a 5% probability level. The fastest radial mycelial growth was observed in semi-solid water agar (AA) for A. musiformis, A. robusta, M. eudermatum, and M. elegans. Furthermore, the same pattern was observed for M. eudermatum and M. elegans incubated in rice water, dextrose, and agar (RDA). The potato dextrose (PD) liquid medium was the most suitable for CFU production.